DETERMINATION OF PARAMETERS OF THE TRACK CIRCUIT DURING THE MEASURING WITH THE MOBILE LABORATORY - Serdiuk, T. M.; Gavryliuk, V. I. (Science and Transport Progress, 2005)
A method is proposed for determination of rail circuits parameters in measurements with the use of automated microprocessor system, installed in a laboratory car. The system allows to check and measure the parameters of current in the rail circuits. The value of primary and secondary parameters of the rail circuits is determined by the data of measurement of code current in rails.